2018
DOI: 10.1097/cji.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Efficacy of Treatment With the Anti-PD-1 Mab Nivolumab in Radiation and Multichemorefractory Advanced Penile Squamous Cell Carcinoma

Abstract: Penile squamous cell carcinoma (PeSCC) is a rare tumor and advanced PeSCC is associated with poor survival due to the aggressiveness of the disease and lack of effective systemic therapies. We describe for the first time a case with advanced chemoradiation refractory PeSCC who had documented response to active immunotherapy with the immune checkpoint inhibitor, anti-programmed death-1 monoclonal antibody Nivolumab. The patient suffered from a poor prognosis human papillomavirus-negative PeSCC, with a somatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Furthermore, high-risk human papilloma virus-negative status (hrHPV) and diffuse PD-L1 expression in the tumor field demonstrated significant correlation with poor disease-specific survival with an HR of 9.73 ( p -value < 0.01), and HR of 2.81 ( p -value=0.03), respectively [ 23 ]. Moreover, in a recent case study, Trafalis et al reported a partial response to nivolumab, an anti-PD-1 monoclonal antibody, in a patient with advanced hrHPV negative penile SCC refractory to chemoradiation therapies [ 34 ]. The authors reported a >80% reduction in tumor volume after eight cycles of nivolumab.…”
Section: Pd-l1 Expressionmentioning
confidence: 99%
“…Furthermore, high-risk human papilloma virus-negative status (hrHPV) and diffuse PD-L1 expression in the tumor field demonstrated significant correlation with poor disease-specific survival with an HR of 9.73 ( p -value < 0.01), and HR of 2.81 ( p -value=0.03), respectively [ 23 ]. Moreover, in a recent case study, Trafalis et al reported a partial response to nivolumab, an anti-PD-1 monoclonal antibody, in a patient with advanced hrHPV negative penile SCC refractory to chemoradiation therapies [ 34 ]. The authors reported a >80% reduction in tumor volume after eight cycles of nivolumab.…”
Section: Pd-l1 Expressionmentioning
confidence: 99%
“…3,9-11 It has been used with some success in metastatic penile cancers, although evidence so far has been restricted to clinical cases. 12,13 However, the rational for its use is sound, as studies have found expression of PD-L1 in 40% of penile SCC. 14 Several phase 2 trials are underway to evaluate the role of immunotherapy in advanced penile cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is detected in 40-60% of PSCC cases and is correlated with poor prognosis and the number of tumor-infiltrating lymphocytes 48 . In a case report, a patient with an HPV-negative PSCC treated with nivolumab experienced a partial response 67 . Currently, there are multiple ICB trials recruiting patients with PSCC (e.g.…”
Section: Discussionmentioning
confidence: 99%